The Role of Experiential Marketing in Building Brand Equity and Customer Loyalty of MSMEs in the Digital Age : A Case Study on International Markets - Muhammad Tody Arsyianto; Sudarmiatin Sudarmiatin (International Forum of Researchers and Lecturers, 2025)
MSMEs face complex challenges in building brand equity and customer loyalty in the digital era, where global competition and dynamic consumer preferences require innovative marketing strategies (Lasrado et al., 2022). This research aims to analyse the role of experiential marketing in improving brand equity and customer loyalty of MSMEs in international markets, with case studies on the creative sector (fashion/culinary) in three regions: ASEAN, Middle East, and Europe. Using an explanatory quantitative approach, data was collected from 400 active customers through a structured questionnaire and analysed with SEM-AMOS. Results show experiential marketing has a significant effect on brand equity. Practical implications include data analytics-based budget allocation recommendations and cultural adaptation in marketing strategies. The findings contribute to the global MSME digital marketing literature and offer operational guidance for businesses.